Comparison between multi-spot laser and conventional laser in treatment of diabetic clinically significant macular edema - Elsawah,Kareem Mohsen (2017)
Abstract Objectives: The purpose of this work is to assess the safety and the efficacy of multi-spot laser in comparison with the conventional laser in the treatment of non-proliferative diabetic retinopathy with CSME in relation to the visual outcome, central macular thickness by (OCT) and the presence of adverse events. Methods: prospective randomized study on total number of 50 eyes divided in two groups each one 25 patients . group A patients underwent focal, grid laser or modified grid macular laser photocoagulation using green laser 532nm GYC-1000. Group B underwent focal ,grid laser or modified grid macular laser photocoagulation multispot laser photocoagulation (VALON TT inclusion criteria was diabetes mellitus type II patients , clinically significant macular edema . patients were monitored by BCVA, OCT, IOP, adverse events pre and 1 week , one month , three months postoperative. Results: The mean preoperative BCVA in group A with conventional laser was 0.294 ± 0.1715 decimal and in group B with multispot laser (valon ) was 0.3040 ± 0.2140 . The mean BCVA 3 months post-laser in group A was 0.4820 ±0.244 decimal and in Group B was 0.5080 ± 0.1977. Central macular thickness of the patients was measured pre-laser and in the follow up periods of 1week, one month, three months. The mean preoperative CMT in Group A was 375.92 ± 65.69 um and in Group B was 361.0± 50.400 um. The mean CMT 3 months post-laser in Group A was 314.44 ±85.938 um and in Group B was 0322.668 ± 57.500 um. The multisport system parameters used higher power of mean 155 mW ± 90.1 more than the conventional laser 100 mW ± 19.4 to produce the same therapeutic visible effect. Conclusion: We found that multisport system is safe, rapid, effective in treatment of clinically significant macular edema in short term follow up periods and had short exposure time. Although the shorter pulse duration of the multisport system necessitates the use of a higher power, it is not associated with adverse effects.